Tren Pemasaran Digital: Analisis Perbandingan Platform Media Sosial Facebook Ads Dan Google Ads - Siti Mulasih; Aep Saefullah (Jurnal Riset Rumpun Ilmu Ekonomi, 2024)
The goal of this study was to analyze the effectiveness trends of digital marketing platforms with a comparison between two platforms, Google Ads and Facebook Ads. This research was conducted in January-February 2024 in East Ciputat District, South Tangerang City. The research subjects were 10 business owners who use both platforms, namely Google Ads and Facebook Ads. This research uses a qualitative method, namely by conducting in-depth interviews with 10 business owners who use both platforms. The results showed that the two platforms have different effectiveness, depending on the type of business and the target market. Google Ads is more effective for businesses that target consumers who are looking for information about certain products or services online. Meanwhile, Facebook Ads are more effective for businesses that target consumers who have a certain interest or interest in a particular product or service. This research implies that business owners need to choose the digital marketing platform that best suits their business type and target market. Choosing the right digital marketing platform will help business owners to increase their marketing effectiveness and achieve their business goals